Strategi Pengembangan Bisnis Irhans Tailor melalui Pendekatan Business Model Canvas - Irfan Ilmi (Pusat Riset dan Inovasi Nasional, 2025)
This research focuses on the analysis of the business development strategy of Irhans Tailor, a local garment manufacturing MSME, using the Business Model Canvas (BMC) approach. Garment manufacturing MSMEs in Indonesia often face serious problems such as low levels of innovation, limited use of digital technology, and weak competitiveness in facing an increasingly competitive market. Although Irhans Tailor has a fairly stable local market share, this business still experiences obstacles in expanding its market reach, establishing sustainable customer relationships, and improving operational efficiency. This research was conducted through library research with a descriptive qualitative approach, which reviewed various relevant literature on business strategy, MSMEs, digitalization, and the implementation of BMC. The analysis results revealed that mapping the nine elements in the BMC provides a comprehensive overview of Irhans Tailor's business conditions and helps formulate a more targeted development strategy. Some recommended strategies include product diversification according to market needs, utilizing digitalization in marketing channels and ordering systems, collaborating with local communities to expand networks, increasing production process efficiency through operational innovation, and strengthening brand identity to build customer loyalty. Thus, this study confirms that BMC not only plays a role as a business analysis tool, but can also be used as a practical guide in forming a more innovative, adaptive to change, and long-term sustainability-oriented MSME business model.